Between low-status ruin and cornerstone of modern Rome: an heritage history of Termini - van Hout, Milou (Incontri. Rivista europea di studi italiani, 2018)
Review of: Arthur Weststeijn & Frederick Whitling, Termini. Cornerstone of Modern Rome, Papers of the Royal Netherlands Institute in Rome Vol. 65, Roma, Edizioni Quasar, 2017, 168 p., ill., ISBN: 9788871408132, € 38,00.